Influence of support acidity on the performance of size-confined Pt nanoparticles in the chemoselective hydrogenation of acetophenone1. Issue 5 (28th May 2015) - Wang, Zichun; Kim, Kyung-Duk; Zhou, Cuifeng; Chen, Mengmeng; Maeda, Nobutaka; Liu, Zongwen; Shi, Jeffrey; Baiker, Alfons; Hunger, Michael; Huang, Jun
<x xml:space="preserve">Abstract</x> Chemoselectivity of hydrogenation depends on strength of the covered BAS, whereas the free BAS enhance the rate.